Evidence-based pediatric oncology - Pinkerton, C. R. (C. Ross), 1950-; Shankar, A. G. (Ananth Gouri), 1962-; Matthay, Katherine (Chichester, West Sussex : Wiley-Blackwell, a John Wiley & Sons, Ltd., Publication : BMJ Books, 2013)
Of previous studiesReferences; New studies; Chapter 10 Non-Hodgkin lymphoma; Commentary by Ross Pinkerton; References; Summary of previous studies; References; New studies; Study 1; Study 2; Study 3; Study 4; Chapter 11 Hodgkin lymphoma; Commentary by Cindy L. Schwartz; Radiation therapy; Combination therapy; Chemotherapy only; References; Summary of previous studies; References; New studies; Study 1; Study 2; Part 2: Leukemia; Section 1: Acute myeloid leukemia; Chapter 12 Acute myeloid leukemia commentary; Induction; Postremission therapy; References.
This book is updated with evidence from the latest published reviews and is more clinically focused, with an emphasis on application of the trial findings. With increased coverage of trials in the area of supportive care for pediatric cancer patients, each chapter opens with a clinical question and concludes with a summary on the trial findings from an expert commentator.
Part 1: Solid tumors. Rhabdomyosarcoma -- Osteosarcoma -- Ewing sarcoma -- Wilms tumor -- Neuroblastoma -- Hepatoblastoma -- Malignant germ cell tumors -- Medulloblastoma -- Glioma -- Non-Hodgkin lymphoma -- Hodgkin lymphoma -- Part 2: Leukemia. Section 1: Acute myeloid leukemia -- Acute myeloid leukemia commentary -- Remission induction in acute myeloid leukemia -- Acute myeloid leukemia consolidation -- Maintenance treatment in acute myeloid leukemia -- Autologous bone marrow transplantation in acute myeloid leukemia -- Acute myeloid leukemia: miscellaneous -- Section 2: Childhood lymphoblastic leukemia -- Childhood lymphoblastic leukemia commentary -- Remission induction in childhood lymphoblastic leukemia -- Central nervous system-directed therapy in childhood lymphoblastic leukemia -- Maintenance treatment in childhood lymphoblastic leukemia -- Relapsed childhood lymphoblastic leukemia -- Postinduction therapy in adolescents and young adults with acute lymphoblastic leukemia -- Part 3: Supportive care in pediatric oncology. Colony-stimulating factors -- Cardioprotection in pediatric oncology -- Infections in pediatric and adolescent oncology.
Includes bibliographical references and index.
Online resource; title from electronic title page (ebrary, viewed on February 24, 2015).
Keywords: Tumors in children; Evidence-based medicine; Clinical trials -- Evaluation; Child; Neoplasms; Evidence-Based Medicine; Evidence-based pediatrics; Neoplasms; HEALTH & FITNESS -- Children's Health; MEDICAL -- Pediatrics; Clinical trials -- Evaluation; Evidence-based medicine; Tumors in children; Tumoren; Kinderen; Evidence-based practice; Case Reports; Electronic books